Assessment Administrative Strategies for Managing Security in Secondary Schools in Kebbi State, Nigeria - Shehu, Bello Gwandu; Asheik , Ali Kime; Danbello , Shehu Yabo (Kashere Journal of Education, 2025)
This study investigated the administrative strategies for managing security in secondary schools in Kebbi State, Nigeria. We formulated three research questions to steer this study. A descriptive research design was also adopted to guide the conduct of this study. The population of the study consists of all the principals and teachers in secondary schools in Kebbi State, Nigeria. A sample of 205 teachers and principals of senior secondary schools were involved in this study across the three educational zones in the state, which were determined using multi-stage sampling and a research advisor table. The instruments for data collection were questionnaires designed by the researcher, titled Administrative Strategies for Managing Security Questionnaire (ASMSQ), Administrative Measures for Enhancing Security Questionnaire (AMESQ), and Community Involvement in Improving Security Management Questionnaire (CIISMQ). These questionnaires were administered to teachers and principals of the sampled schools and were duly validated by experts. Observations, corrections, and suggestions were made, and they were duly effected, which made the instrument valid. The reliability of the instrument was determined using a test-retest method in a pilot study, where it was administered to teachers and principals from two schools not included in the sample. The Pearson product-moment correlation coefficient was used to correlate the test-retest results, yielding reliability indices of 0.88, 0.75, and 0.78. The study adopted a simple statistical method of analysis, which involves using tables, means, and standard deviations to analyse the collected data. The findings of this study revealed that there was a moderate level of administrative strategies applied in managing security in secondary schools in Kebbi State, Nigeria. The researcher recommended that Government and private individuals should provide school-based security guards or present police officers, fencing of schools, staff and visitor ID badges, and enhanced community engagement in secondary schools in Kebbi State, Nigeria.